CAUSES OF DRY EYES AND METHODS OF PREVENTION - Giyazova Malika Mukhamadovna; Bobonazarov Bekzod (World Scientific Research Journal, 2025)
Abstract: The causes of dry eyes include factors such as prolonged screen viewing, dry air, contact lens use, hormonal changes, and the effects of medications. And also recommends important measures to reduce dry eyes, such as changing the screen usage mode, blinking your eyes regularly, increasing air humidity, using artificial tear drops, and eating a healthy diet. With these recommendations, you can maintain natural eye moisture and prevent discomfort.